PERANCANGAN APLIKASI PENGARSIPAN BERKAS DSO GURU BERBASIS WEB (STUDI KASUS: SMK MUHAMMADIYAH 2 KUNINGAN) - Krisdiawan, Rio Andriyat (TI S1 FKOM UNIKU, 2015)
AbstractInside An organization / institution in which there are labor / employee are important documents of the employees in it. Activity in school SMK Muhammadiyah 2 Kuningan could not be separated with the activities of labor / employee in it, including the documentation of the teaching force, be it filing certificate, decree, until the letter of assignment and a seminar attended by the teaching staff. Archiving documents (DSO) is usually done manually stored and managed by the administrative staff. The archiving process is still manual that cause a variety of problems that often occur as the number of the document to be archived, the time required in the search process files, up to a lecturer who did not report the files relating to the institution, such as education and seminars have been followed. Application design data file on a web-based school teacher SMK Muhammadiyah 2 Kuningan provides applications to manage, store and search the data files of teachers in SMK Muhammadiyah 2 Kuningan. In this application the faculty will be given access rights to login to update your personal file with upload to the system in the form of image format scanning results. Further, the application was built to help manage the archiving process data file teachers become more effective and efficient. This application is designed to use web-based programming language that is PHP and the MySQL database, to be accessible to all faculty anywhere and anytime. System development method used in this application development using RUP (Rational Unified Process).Â Keyword: Archiving DSO, SMK Muhammadiyah 2 Kuningan, web programming, php, MySQL